Interlinkages among Terrorism, Macroeconomic Instability, Political Instability, and Economic Growth in Pakistan - Ayesha Naz; Hafsa Jabeen; Azra Nasir (NUST Journal of Social Sciences and Humanities)
This study attempts to establish the relationship between three types of instabilities and economic growth. Political instability, macroeconomic instability, terrorism, and economic growth are analyzed for the period of 1970 to 2019 in Pakistan. The study constructs the indices of the above-mentioned variables by adding some new variables. Results show that terrorism, political instability, macroeconomic instability, and GDP per capita have long-run associations. GDP per capita and political instability is positively related to terrorism. It indicates that political instable environment paves the way for terrorists to achieve their targets in Pakistan. However, the positive association of GDP per capita to terrorism is due to uneven income distribution pattern. It stimulates deprived groups to become a part of violent activities. Furthermore, results show that macroeconomic performance of a country has no significant effect on terrorist activities but persistent poor performance increases the probability of terrorism. Therefore, in the long-run, macroeconomic instability has positive influence on terrorism. Causality relationships indicate no link between political instability and macroeconomic instability. However, terrorism causes both political and macroeconomic instability in Pakistan.